Measuring and Mapping Food Security Status of Rajasthan, India: A District-Level Analysis - Jatav, Surendra Singh; Nayak, Sanatan; Singh, Naveen Prakash; Naik, Kalu (Frontiers in Sustainable Food Systems, 2022)
The present study tries to analyse the status of food security along with its various components such as food availability, accessibility, and stability with the help of a multidimensional index across districts of Rajasthan, India based on an indicator approach. QGIS mapping computer application and quintile method was used to map districts into low, medium, high and very high categories Furthermore, multiple regression analysis was applied to find out the significant determinants of food security and its respective components. The results confirm that there is a wide range of inequalities in terms of food security and its components: availability, accessibility, and stability across districts. It was found that Ganganagar district (0.407) was rated the most food-secure district due to relatively higher food stability (0.401) in the Rajasthan state and on the contrary, lower food availability (0.084) and accessibility (0.183) contributed to the lowest food security in Dungarpur district. Moreover, districts associated with dry regions are highly vulnerable and relatively less food secure compared to districts having surface irrigation facilities. Hence, the study recommends; diversification from farm to non-farm activities; sufficient storage capacity to control price fluctuations throughout the year, formulation and dissemination of climate-resilient technologies; investment in infrastructure, promotion of water management and conservation technologies, and regulation and replenishment of groundwater in rural areas for augmenting cropping intensity; district-specific policies to arrest food insecurity; strengthening coverage of rural employment programme, i.e. MGNREGA.